2004
DOI: 10.1093/bioinformatics/bth448
|View full text |Cite
|
Sign up to set email alerts
|

Advances to Bayesian network inference for generating causal networks from observational biological data

Abstract: http://www.jarvislab.net/Bioinformatics/BNAdvances/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
427
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(438 citation statements)
references
References 21 publications
7
427
0
4
Order By: Relevance
“…Previous studies by Cantone et al [12] had suggested that DBNs (BANJO [43]) performed better than Table 2. Average area under the receiver operating characteristic curve (AUROC) and area under the precision-recall (AUPR) curve (in brackets) for each of the 100-gene DREAM4 networks using various inference algorithms.…”
Section: 21mentioning
confidence: 81%
“…Previous studies by Cantone et al [12] had suggested that DBNs (BANJO [43]) performed better than Table 2. Average area under the receiver operating characteristic curve (AUROC) and area under the precision-recall (AUPR) curve (in brackets) for each of the 100-gene DREAM4 networks using various inference algorithms.…”
Section: 21mentioning
confidence: 81%
“…Examples of such methods include principal component analysis (PCA) and hierarchical clustering (HC) to identify potentially co-expressed genes over the different combinatorial growth conditions. In addition, Bayesian network (BN) analysis can be used to infer regulatory linkages between mRNA abundances (Friedman, 2004;Hurley et al, 2012;Sachs et al, 2005;Yu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although such comparison was reported before [36,37], an important fact was neglected, that gene expression time series data are far shorter from other biological time series data such as neuron data. For example, DBNs implementation is usually designed for hundreds or thousands of samples, e.g., the 2000 sample points of simulated data in [36,38]. Limitation of microarray experimental costs prohibits such technique from exploring gene expression data.…”
Section: Experiments On Synthetic Datamentioning
confidence: 99%